مقامات مدني صالح – دراسة نحوية "مقامات من الاشتات إنموذجًا" - علي, نور جبار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study, entitled “The Maqamat of Madani Saleh: A Grammatical Study - Maqamat from Al-Ishtaat as a Model,” is a research paper that reveals the grammatical structure of modern Arabic maqamat through a detailed analysis of one of Madani Saleh's most prominent maqamat. The research aims to study the grammatical features that distinguish this literary form and highlight how grammatical structures contribute to the aesthetic and rhetorical impact of the text. The study is divided into two main sections. The first chapter presents a theoretical framework discussing the development of modern maqamat, their stylistic features, and the role of Arabic grammar in shaping narrative discourse and its relationship to literature. It also provides a brief overview of the author of the maqama and his life. The second chapter provides a practical analysis of the maqamat “Maqamat min al-Ishtaat,” focusing on the grammatical patterns found in the text. The study extracts and examines various grammatical structures and analyzes their rhetorical functions, showing how they contribute to creating irony, exaggeration, temporal shifts, and stylistic surprises. These elements reflect the author's deliberate use of grammar as a creative and expressive tool. The study concludes that grammar in Madani Salih's maqamat is not merely a structural necessity, but a vital element of artistic expression. His use of grammar enhances the textual meaning and reveals a deep linguistic awareness that links traditional grammar with modern literary creativity.